Niveles de mercurio total en Aequidens Rivulatus (vieja) en el Río Carrizal del Cantón Bolívar, Manabí-Ecuador. - Moreira Calderón, Marley Viviana (2018)
The research focused on the determination of total mercury levels in Aequidens rivulatus (vieja) in the Carrizal del Cantón Bolívar river in the province of Manabí, by quantifying mercury levels in muscle, liver and gills and their relationship with morphological characteristics. (weight and length). It was executed as non-experimental research, with the quantitative and qualitative methods that served to diagnose this problem. The biogenetic characteristics of the species were described and analyzed, in addition to the physical and taxonomic classification as a basis, information necessary for the evaluation of mercury accumulation. Sampling was carried out through the establishment of nine sampling stations, taking two species at each established point, taking a total of eighteen specimens during the rainy and dry season. The results identified, that, the levels of mercury detected in the fish samples, corresponding to the two months of sampling, resulted in figures that are below and other figures that exceed the permissible limit (0.5 ppm) according to the regulations international and it was also found that the samples with the highest concentration were found in the month of August, in the muscle with 4,036 ppm, in the E7 station, taken in the sector of San Bartolo. In addition, a significant relationship between weight and length was observed with the accumulation of mercury in the muscle and liver of the fish in October, while in August there was no relationship between weight and length with the concentration of mercury in the target organs. Concluding that morphological characteristics (weight and length) with an average length of 153.88 mm and weight 128.61g showed variation according to each sample executed and had a great influence with the mercury levels found in the fish of the nine stations raised on the Carrizal river.